Effect of pre-operatory low-level laser therapy on pain, swelling, and trismus associated with third-molar surgery - Petrini, Morena (Med Oral Patol Oral Cir Bucal, 2017)
BACKGROUND: The extraction of impacted third molars is commonly associated to pain, edema, trismus, limited jaw opening and movements. The aim of this retrospective study is to verify if pre-surgical low-level laser therapy (LLLT) associated with the extraction of impacted lower third molars could add benefits to the postoperative symptoms respect LLLT performed only after surgery. MATERIAL AND METHODS: Data from 45 patients subjected to a surgical extraction of lower third molars were pooled and divided into three groups. Patients that received only routine management were inserted in the control group. Group 1, were patients that received LLLT immediately after surgery and at 24 hours. In group 2 were included patients treated with LLLT immediately before the extraction and immediately after the end of the procedure. Data were analyzed using linear regression and descriptive statistics. RESULTS: Both laser-treated groups were characterized by minor events of post-surgery complications of pain, edema, trismus. The use of NSAIDs in the first 24 hours was significantly inferior in Group 2. CONCLUSIONS: Pre-surgical LLLT treatment seems to increase the analgesic effect of LLLT. However, trismus and edema were reduced in both laser treated groups, independently from the period of irradiation. Key words:Laser, LLLT, pain, surgery, extraction, third molars, wisdom teeth.